S. Daukanto didžiojo lenkų-lietuvių kalbų žodyno istorija - Subačius, Giedrius (Kalbotyra, 1990)
An attempt is made to describe the history of manuscript of the main dictionary (1850-1856) of Simonas Daukantas, i.e. to show when and where the manuscript was created and what fate it suffered from the time of its creation till nowadays. It is also shown to what extent the vocabulary of the Daukantas’s dictionary has penetrated into Lithuanian linguistic literature. It is argued that quite a lot of words of the dictionary haven’t penetrated into scientific circulation yet.